P0990RENINAAV DOSE-DEPENDENTLY EXACERBATE ALBUMINURIA AND GLOMERULOSCLEROSIS, AND REDUCE GFR IN FEMALE UNINEPHRECTOMIZED DB/DB MICE. (6th June 2020) - Østergaard, Mette Viberg; Ida, Rune; Pedersen, Annemarie Aarup; Secher, Thomas; Sembach, Frederikke Emilie; Thrane, Sebastian Tølbøl; Roostalu, Urmas; Fosgerau, Keld; Fink, Lisbeth N; Vrang, Niels
Abstract: Background and Aims: Diabetic nephropathy (DN) is a long-term complication that occurs in ∼40% of diabetes patients and is a leading cause of end-stage renal disease. Despite recent emergence of SGLT2 inhibitors and GLP-1 receptor agonists for nephroprotection in diabetes patients, drug discovery has been halted by the lack of reliable rodent models exhibiting features of human DN. In a newly established mouse model of progressive DN, we investigate the effects of hypertension on kidney injury. Method: Female db/db mice were uninephrectomized (UNx) at 8 weeks of age and injected i.v. with a Renin adeno-associated virus (AAV) construct at different doses to induce hypertension, while a LacZAAV construct was used as negative control. db/+ mice served as healthy controls. Hypertension was measured by tail cuff and glomerular filtration rate (GFR) transcutaneous recoding of FITC-sinistrin after i.v. bolus injection at 22 weeks of age. Urine ACR measured in spot urine samples collected before termination 24 weeks of age. Terminal kidney samples were collected for 3D image analyses, histopathological evaluation, and next generation sequencing for gene expression analyses. Results: GFR measurements indicated hyperfiltration in all AAV-injected UNx db/db mice compared to db/+ mice, while ReninAAV tended to dose-dependently decrease GFR compared to LacZAAV in UNx db/db mice. Urine ACR was worsened by ReninAAV-induced hypertension compared to LacZAAV controls. Automized AI-based glomerulosclerosis scoring showed ReninAAV dose-dependent increases in glomerulosclerosis compared to LacZAAV controls. 3D kidney imaging demonstrated increased glomerular volume in LacZAAV UNx db/db mice compared to db/+ mice with no further effect in ReninAAV groups. RNA sequencing revealed upregulated gene expression markers of fibrogenesis (incl. Col1a1, Col3, Col4, Fn1, Lamc2 and Vim ) and tubular injury markers ( Ngal and Kim-1 ), as well as downregulation of proximal tubular markers ( Megalin and Aqp1 ) in ReninAAV UNx db/db mice compare to LacZAAV controls. Conclusion: ReninAAV-induced hypertension in female UNx db/db mice accelerates kidney injury in uninephrectomized db/db mice and aggravates GFR, albuminuria and glomerulosclerosis in parallel with increased expression of genes associated with tubular injury renal fibrosis. Together, these data confirm that ReninAAV UNx db/db mice is a reliable model of DN with features of late stage human disease.